2006
DOI: 10.1097/01.blo.0000183739.50869.bb
|View full text |Cite
|
Sign up to set email alerts
|

Heat Generated by Knee Prostheses

Abstract: Temperature sensors were placed in 50 knees in 25 patients who had one or both joints replaced. Temperature recordings were made before walking, after walking, and after cycling. The heat generated in healthy, arthritic, and replaced knees was measured. The knee replacements were done using eight different prostheses. A rotating hinge knee prosthesis generated a temperature increase of 7 degrees C in 20 minutes and 9 degrees C in 40 minutes. An unconstrained ceramic femoral prosthesis articulating with a polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Randomized comparison studies in which patients received a bicruciate-retaining knee prosthesis on one side and a posterior cruciate-retaining or substituting prosthesis on the other side have shown that 76% of patients prefer the bicruciate-retaining prosthesis [16,18]. Comparison studies I have done also show there is less noise, less heat generated, and less bone loss with a bicruciate-retaining prosthesis compared with other designs [17,19]. A TKA with a bicruciate-retaining prosthesis necessitates close approximation of the prosthesis to the anatomic contours, meticulous alignment technique, and preservation of well-balanced cruciate and collateral ligaments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Randomized comparison studies in which patients received a bicruciate-retaining knee prosthesis on one side and a posterior cruciate-retaining or substituting prosthesis on the other side have shown that 76% of patients prefer the bicruciate-retaining prosthesis [16,18]. Comparison studies I have done also show there is less noise, less heat generated, and less bone loss with a bicruciate-retaining prosthesis compared with other designs [17,19]. A TKA with a bicruciate-retaining prosthesis necessitates close approximation of the prosthesis to the anatomic contours, meticulous alignment technique, and preservation of well-balanced cruciate and collateral ligaments.…”
Section: Discussionmentioning
confidence: 93%
“…Although the ACL is functional in more than 60% of patients undergoing a TKA [1,7,8] and kinematic studies support the concept of bicruciate-retaining (that is, ACLpreserving) TKA [14,23], few studies have evaluated patients treated with bicruciate-retaining TKA implants [16][17][18][19]21]. Because of these perceived advantages, I used a bicruciate-retaining TKA implant in my practice for all patients with an intact ACL and acceptable deformity during a 3-year period, and because of the limited number of studies available at longer term [21], I sought to evaluate their performance and durability.…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant, as a temperature rise of 9°C after 40 min of walking was measured in artificial knees in vivo. [37] Our findings show the need to identify and validate the temperature dependent mechanical properties of UHMWPE that can lead to more accurate predictions of heat dissipation and combined temperature-dependent deformation. This will allow the prediction of long-term performance of implants more precisely and even give paradigms for designs that improve heat dissipation for more active younger persons.…”
Section: Discussionmentioning
confidence: 89%
“…While well known complications, such as continued pain and restricted mobility [11] and stiffness [19], are included, so too are lesser known/unreported ones. These include relevant complications for rehabilitation such as depression and panic attacks following surgery [20], early falls [21], later falls, heat [22] and ankle pain. The data in Table 1 relates to complications identified from the literature before the start of the study.…”
Section: Discussionmentioning
confidence: 99%